Improved Access to Behavioral Health Care for Patients in a Large New York City Behavioral Health Clinic by the Transition to Telemedicine - Aaron Reliford; Emily Zhang; Anni Liu; Olga Lanina; Sharifa Z. Williams; Navin Sanichar; Shabana Khan; Isaac Dapkins; William Gordon Frankle (Telemedicine Reports)
Objective: To examine the transition to telemental health within the behavioral health program of a large federally qualified health center, The Family Health Centers at NYU Langone, in the 3 months following the onset of the COVID-19 pandemic—specifically impacts on show rates and access to care. Methods: Demographic and clinical information for all scheduled visits was collected for two time periods: the telemental health period, March 16, 2020-July 16, 2020 (46,878 visits, 5,183 patients), and a comparison period, March 15, 2019-July 16, 2019 (47,335 visits, 5,190 patients). Data collected included modality, appointments scheduled/completed/cancelled/no-showed, age, gender, race, language, and diagnosis. Generalized estimating equations with a compound symmetry correlation structure and logit link were used for analysis. Results: An ∼twofold increase in the likelihood of completing a visit in 2020 vs. 2019 (adjusted OR = 1.92, p < 0.001) was observed. Patients who received treatment in both time frames (n = 2,961) also showed increased completion rates in 2020 vs. 2019. No diagnostic group had a decline in competition rate from 2019 to 2020, including those with severe mental illnesses, although patients with schizophrenia were significantly less likely to complete an initial visit in 2020 compared with 2019 (adjusted odds ratio, aOR = 0.37, p < 0.001). For those with appointments in both timeframes, we noted a significant association between gender and completion rate in 2019 (male 66.5% ± 25.1% vs. female 64.2% ± 24.4%, ANOVA p = 0.01), which was eliminated by implementation of telemental health. Conclusions: This study supports the use telemental health to increase access for all patients, including those from under-represented, lower socioeconomic status backgrounds.